Impaired angiogenesis in the enalapril-treated neonatal rat kidney - Hyung Eun Yim; Kee Hwan Yoo; Eun Soo Bae; Young Sook Hong; Joo Won Lee (Korean Pediatric Society, 2016)
PurposeNephrogenesis is normally accompanied by a tightly regulated and efficient vascularization. We investigated the effect of angiotensin II inhibition on angiogenesis in the developing rat kidney.MethodsNewborn rat pups were treated with enalapril (30 mg/kg/day) or vehicle (control) for 7 days after birth. Renal histological changes were checked using Hematoxylin & Eosin staining. We also investigated the intrarenal expression of vascular endothelial growth factor (VEGF)-A, VEGF receptor 1 (VEGFR1), VEGFR2, platelet-derived growth factor (PDGF)-B, and PDGF receptor-β with Western blotting and immunohistochemical staining at postnatal day 8. Expression of the endothelial cell marker CD31 was examined to determine glomerular and peritubular capillary density.ResultsEnalapril-treated rat kidneys showed disrupted tubules and vessels when compared with the control rat kidneys. In the enalapril-treated group, intrarenal VEGF-A protein expression was significantly higher, whereas VEGFR1 protein expression was lower than that in the control group (P<0.05). The expression of VEGFR2, PDGF-B, and PDGF receptor-β was not different between the 2 groups. The increased capillary CD31 expression on the western blots of enalapril-treated rat kidneys indicated that the total endothelial cell protein level was increased, while the cortical capillary density, assessed using CD31 immunohistochemical staining, was decreased.ConclusionImpaired VEGF-VEGFR signaling and altered capillary repair may play a role in the deterioration of the kidney vasculature after blocking of angiotensin II during renal development.